SEMANTIC AND MORPHOLOGICAL TECHNIQUES OF PSYCHOPATHS IN DARK MATTER YOUTUBE CHANNEL - Indah Maria Ulfa; Rohmani Nur Indah (CALL, 2020)
The brain of psychopaths may differ from normal individuals in terms of their cerebral organization of language. Psychopaths have a different way of communicating their ideas within their minds. There is a distinct technique of psychopathic language which can be identified. Therefore, this study examines the kinds of speech techniques of psychopaths. It aims at discovering the semantic and morphological techniques used by four psychopaths in the Dark Matter YouTube channel. Methodologically, this study is categorized as descriptive qualitative research. The data were in the form of utterances by four psychopaths in Dark Matter channel posted on October 10, 2019. There were sixteen data in the form of utterances which contained kinds of the speech technique used by psychopaths. The researchers calculated the data by observing, transcribing, describing, and analyzing the speech of psychopaths in the Dark Matter channel. Further, the data were classified by using Timor and Weiss (2008) patterns of psychopathic knowledge. The results showed that four psychopathic individuals demonstrated the kinds of speech technique, which has a distinct pattern using semantic and morphological techniques. Based on semantic technique, all categories found in the data are vocabulary, repetition, figurative language, positive and negative connotations, and anaphora. The result also shows three categories of morphological techniques: nominalization, passivization, and first-person plural. This study is expected to be a reference for further researcher for analyzing the phenomena of psychopathic language. Keywords: semantic techniques, morphological technique, psychopathic language, psychopaths